2019
DOI: 10.21315/mjms2019.26.6.3
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Quercus infectoria (Olivier) Galls as a Resource for Anti-parasitic Agents: In Vitro and In Vivo Studies

Abstract: Parasitic diseases represent one of the causes for significant global economic, environmental and public health impacts. The efficacy of currently available anti-parasitic drugs has been threatened by the emergence of single drug- or multidrug-resistant parasite populations, vector threats and high cost of drug development. Therefore, the discovery of more potent anti-parasitic drugs coming from medicinal plants such as Quercus infectoria is seen as a major approach to tackle the problem. A systematic review w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…To date, neither studies of the antimalarial activity nor the mechanism of the Q. infectoria galls are evident in the literature (Nik Mat Zin et al, 2019). In this work, the evidence of the antimalarial effect of the acetone crude extract on pH of the malaria parasite's digestive vacuole was provided.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…To date, neither studies of the antimalarial activity nor the mechanism of the Q. infectoria galls are evident in the literature (Nik Mat Zin et al, 2019). In this work, the evidence of the antimalarial effect of the acetone crude extract on pH of the malaria parasite's digestive vacuole was provided.…”
Section: Discussionmentioning
confidence: 93%
“…Quercus infectoria (Olivier) (Fagaceae) is one of the medicinal plants traditionally used in folk medicines for post-partum medication and various ailments (Umachigi et al, 2008;Vuthikunchai & Suwalak, 2008;Aroonrerk & Kamkaen, 2009;Jamal et al, 2011). The galls of the plant have a broad spectrum of antimicrobial properties (Hussein et al, 2000;Sawangjaroen et al, 2004;Sawangjaroen & Sawangjaroen, 2005;Ozbilgin et al, 2013;Baharuddin et al, 2014;Kheirandish et al, 2016;Mustafa et al, 2018;Nik Mat Zin et al, 2019). Our recent finding reported that the gall acetone crude extract possesses a promising antimalarial activity in vitro (IC 50 = 5.85 ± 1.90 μg/mL) against the chloroquine-sensitive strain (3D7) of P. falciparum (Nik Mat Zin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, secondary metabolites from natural products have been considered as an option to develop new drugs against Leishmania infections [ 15 , 16 ]. In recent years, significant progress has been made in mitigating the threat of Leishmania parasites.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above points, the dimer interface of LmTIM (Figure 1) has been highlighted as a site of interest in discovering specific compounds that inhibit its function by disrupting its interface. On the other hand, secondary metabolites from natural products have been considered as an option to develop new drugs against Leishmania infections [15,16]. In recent years, significant progress has been made in mitigating the threat of Leishmania parasites.…”
Section: Introductionmentioning
confidence: 99%
“…This compound has been reported to have a number of biological activities such as anticarcinogenic ( 13 ), anti-inflammatory ( 14 ) and antimalarial properties ( 15 17 ). The abundance of pyrogallol ( 18 – 20 ) and ellagic acid ( 21 – 23 ) in Quercus infectoria , an oak species, might contribute to the activity against the malaria parasite ( 24 25 ). Ellagic acid has been postulated to have the antimalarial effect through impairment of the haemoglobin degradation and β-haematin formation in the parasite’s digestive vacuole ( 15 16 , 26 ).…”
Section: Introductionmentioning
confidence: 99%